THE INFLUENCE OF CALCIUM HYPOCHLORITE DOSAGE ADJUSTMENT ON TAPIOCA WASTEWATER PRE-CHLORINATION TOWARD EFFICIENCY OF ACTIVATED SLUDGE TREATMENT - Happy Mulyani; Guruh Sri Pamungkas (Universitas Jenderal Soedirman, 2016)
The objectives of this research are to study about influence of calcium hypochlorite dosage adjustment on tapioca wastewater chlorination toward efficiency of activated sludge treatment especially at MLVSS profile and percentage of COD removal. This research mainly divided into pre-chlorination and activated sludge treatment. Pre-chlorination taken place for 60 minutes at pH 8. The variation of calcium hypochlorite dosages which used are 58, 59, and 60 mg/L. Pre-chlorination effluent with no free chlorine residual then becomes activated sludge treatment influent. Sampling has done each aeration time interval 0, 2, 4, and 6 hour for analysis of COD and MLVSS content. Research result generally shows that addition of aeration time for each variation of calcium hypochlorite dosage will increase MLVSS and decrease COD content. Smallest value of COD effluent could achieved in the activated sludge treatment with calcium hipochlorite dosage 60 mg/L addition at influent during 4 hours aeration time. Addition of 58 mg/l calcium hypochlorite results highest MLVSS and percentage of COD removal.